Kejang pada Tuberkuloma Intrakranial dengan Tuberkulosis Diseminata dan Herpes Zoster Konkomitan: Suatu Pertemuan Klinis yang Jarang - Putu Ayu Diah Meita Wulandari; I Ketut Sumada; Desie Yuliani; Ni Made Kurnia Dwi Jayanthi; Yoanes Gondowardaja (Aesculapius Medical Journal, 2026)
ABSTRACT Background: Disseminated tuberculosis (TB) with central nervous system involvement represents a severe form of extrapulmonary TB that may lead to intracranial tuberculoma and provoke seizures. Herpes zoster coinfection reflects impaired cellular immunity and is rarely reported concurrently, posing diagnostic and therapeutic challenges. Case Presentation: A 71-year-old man presented with two episodes of focal to bilateral tonic seizures. The patient had a history of miliary TB and was undergoing continuation-phase anti-tuberculosis therapy. Herpes zoster lesions appeared one week prior to admission. On presentation, the patient was stuporous but later improved without focal neurological deficits. Head CT revealed multiple bilateral parietal hypodense lesions, while previous MRI findings were suggestive of multiple intracranial tuberculomas. HIV status was non-reactive. Discussion: Seizures in elderly patients are often associated with structural brain lesions, including tuberculomas resulting from hematogenous spread of disseminated TB and formation of Rich foci. Inflammatory edema and caseous necrosis contribute to decreased seizure threshold. The coexistence of herpes zoster indicates cellular immune dysregulation in elderly patients even in the absence of HIV infection. Conclusion: The combination of seizures, multiple intracranial tuberculomas, disseminated TB, and herpes zoster is rare but clinically important. Neuroimaging evaluation and comprehensive management are essential to improve clinical outcomes. Keywords: Disseminated tuberculosis, tuberculoma, seizures, herpes zoster, central nervous system infection.